2015
DOI: 10.1016/j.bpj.2014.11.1962
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Organization of the Plasma Membrane

Abstract: The ESCRT pathway mediates a series of important cellular membrane remodeling and fission events, including cytokinetic abscission. During these processes, ESCRT-III family proteins, including CHMP1B and IST1, form filaments that appear to constrict membranes and facilitate fission. Here, we report the first structure of ''open'' and assembled ESCRT-III proteins. Nearatomic resolution electron cryomicroscopy reveals that filaments comprise a copolymeric assembly of an open conformation inner strand and, unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(61 citation statements)
references
References 0 publications
3
58
0
Order By: Relevance
“…It is generally accepted that cellular membranes are asymmetric bimolecular leaflets composed predominantly of phospholipids, varying concentrations of cholesterol, other minor species of lipids, and a plethora of proteins (1,61,62). Because of its fast flip-flop rate, the cholesterol distribution across the two leaflets of the plasma membrane has been quite challenging to determine, with experiments suggesting either an outer or inner leaflet enrichment (23,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is generally accepted that cellular membranes are asymmetric bimolecular leaflets composed predominantly of phospholipids, varying concentrations of cholesterol, other minor species of lipids, and a plethora of proteins (1,61,62). Because of its fast flip-flop rate, the cholesterol distribution across the two leaflets of the plasma membrane has been quite challenging to determine, with experiments suggesting either an outer or inner leaflet enrichment (23,63).…”
Section: Discussionmentioning
confidence: 99%
“…Because of its fast flip-flop rate, the cholesterol distribution across the two leaflets of the plasma membrane has been quite challenging to determine, with experiments suggesting either an outer or inner leaflet enrichment (23,63). A recent study, based on a large scale molecular dynamics simulation, showed an asymPlasma Membrane Cholesterol in Steroidogenesis DECEMBER 9, 2016 • VOLUME 291 • NUMBER 50 metrical distribution of cholesterol, in which the outer leaflet of the plasma membrane included 54% of the total cholesterol with a slightly higher cholesterol content than the inner leaflet (comprising 46%) (62).…”
Section: Discussionmentioning
confidence: 99%
“…Hydrocarbons May Induce Membrane Flexibility by Accumulating within the Lipid Bilayer Molecular dynamics simulations have become an invaluable technique used to investigate the nanoscale organization of lipid membranes (Marrink et al, 2009;Vattulainen and Rog, 2011), particularly in complex membrane systems (Ingólfsson et al, 2014;Manna et al, 2014). In order to understand how hydrocarbons could affect membrane properties, a novel symmetrical membrane model system was simulated based on the pseudoatomistic Martini force field, with an approximately 4:1 mapping of heavy atoms to coarse-grained particles (Supplemental Fig.…”
Section: The Absence Of Hydrocarbons Has Minor Effects On Photosynthementioning
confidence: 99%
“…E06 mAb binds several by-products of the oxidation of phosphatidylcholine, often referred to as Ox-PC (51). Because phosphatidylcholine is a major component of the outer leaflet of the plasma membrane, it seemed reasonable that this antibody might be sufficient to display an effect (52). Cells were pretreated with E06 mAb (50 g/ml) or a control IgM monoclonal antibody not targeting oxidized lipids (its epitope are advanced glycation end products) (41).…”
Section: Identification Of Efficient Cpps and Robustmentioning
confidence: 99%